Advances in Polygonatum sibiricum polysaccharides: Extraction, purification, structure, biosynthesis, and bioactivity - Liu, Dan; Tang, Wei; Han, Chao; Nie, Shaoping (Frontiers in Nutrition, 2022)
Polygonatum sibiricum has been used as food and medicine for thousands of years, and P. sibiricum polysaccharides (PSPs) have become the hot research spot due to its various health-promoting functions. Numerous studies have shown that PSPs possess huge potential in application of functional food and medicine fields. However, the research status and features of preparation process, molecular structure, and bioactivities of PSPs are unclear. Therefore, this review makes a comprehensive summary and proposes new insights and guidelines of extraction, purification, structural features, biosynthesis, and multiple bioactivities of PSPs. Notably, it is concluded that PSPs mainly contain several types of polysaccharides including fructan, pectin, galactomannan, glucomannans, arabinogalactan, galactan, and have multiple-bioactivates including osteogenic activity, anti-obesity, anti-diabetes, anti-depression, antioxidant, antiglycation, protective effect against neurotoxicity and gut microbiota regulating activity, etc. This review contributes to structure-function study and resource utilization of P. sibiricum and its polysaccharides in food fields.